INNOVATIVE ENSURANCE OF SUSTAINABLE DEVELOPMENT OF BUSINESS STRUCTURES IN UKRAINE: DIGITAL TRANSFORMATION OF HUMAN RESOURCES - Зелінська, Галина Олексіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
The article is devoted to the role of human resources, taking into account the processes of digitalization of business processes at enterprises in the context of innovative changes. Particular attention is focused on the changes taking place in the consciousness of human potential, the formation of its digital skills at enterprises in the context of sustainable development of Ukraine. The special role of education in innovative provision of sustainable development of the functioning of business structures is emphasized. It is determined that the digitalization of innovative activity determines the need to revise the established systems of employee motivation, since both the nature of work and employees’ expectations regarding the organization of work processes are changing. It is determined that digital competence is the basis for the successful functioning of an enterprise and the management of its business processes in conditions of sustainable development. It is found that the innovative activity of business structures in Ukraine is characterized by the integration of such technologies as artificial intelligence, big data, cloud computing, the Internet of Things and blockchain into the innovation management system. It is determined that the theoretical basis of the study of digitalization is based on the concept of digital transformation, which involves not only technological changes, but also a fundamental restructuring of business models, organizational culture and human resource management systems. Attention is focused on the fact that digitalization is today a sought-after factor in the use of human resources in the labor market. It is determined that the issue of developing and implementing digital transformation of business processes in the activities of Ukrainian business entities has become extremely relevant. At the same time, the problem of digital transformation of the person himself among scientists, his achievement of sufficient digital literacy, and the development of digital skills are not sufficiently covered. It is emphasized that the digital transformation of human potential is a multidimensional process that includes not only technological aspects, such as mastering new software products or technical means, but also profound cultural, psychological and organizational changes that require a revision of traditional models of personnel management, motivation systems, etc. In writing the article, both Internet sources were used to reveal the essence of the role of human potential in the context of the growing informatization of business processes, and methods of economic analysis - comparison - to analyze global trends in the development of human resources; a scenario approach - to reveal the priority of a person in decision-making; an abstract-logical approach - to formulate conclusions from the study.